2009
DOI: 10.1590/s0103-863x2009000100012
|View full text |Cite
|
Sign up to set email alerts
|

Paternidade contemporânea: levantamento da produção acadêmica no período de 2000 a 2007

Abstract: Resumo: Este estudo teve como objetivo verificar a incidência de artigos internacionais e nacionais sobre o tema paternidade no período de 2000 a 2007 indexados nas bases de dados: LILACS, SciELO, Web of Science, MEDLINE, Redalyc. Um total de 2.205 trabalhos foi identificado, sendo analisados 353 artigos em relação ao ano de publicação, país, método e temática. Os resultados apontam para significativa produção internacional e nacional, destacando-se EUA, Inglaterra e Brasil. Verificou-se que o tema paternidade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
24

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 86 publications
1
8
0
24
Order By: Relevance
“…This fi nding corroborates the results of the studies of Bronfenbrenner (2005), Souza and Benetti, (2009) and Turcotte and Gaudet (2009), in which the authors concluded that the participation of the father in family life is related to the number of hours he spends working and, therefore, the father needs time to construct his paternity. Thus, the more the father invests time and energy in his work, the less he actively engages in the lives of his children.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This fi nding corroborates the results of the studies of Bronfenbrenner (2005), Souza and Benetti, (2009) and Turcotte and Gaudet (2009), in which the authors concluded that the participation of the father in family life is related to the number of hours he spends working and, therefore, the father needs time to construct his paternity. Thus, the more the father invests time and energy in his work, the less he actively engages in the lives of his children.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the recognition that, in Western societies, the father plays an important role in child development and even though the transformations through which the ideal of fatherhood is passing have paved the way for research in the area (Souza & Benetti, 2009), there is lack of studies that aim to investigate the specifi c aspects of child development in which the paternal fi gure exerts signifi cant infl uence. Furthermore, although some studies indicate an association between paternal behavior and childhood aggressiveness, there is still no clarity on what the activities in which the father engages are that actually help regulate the aggressive behavior of the children.…”
mentioning
confidence: 99%
“…Antes atrelada à divisão sexual do trabalho, a paternidade se fundia à capacidade de prover financeiramente a família, independentemente da relação concreta do pai com seus filhos e filhas. Atualmente, o leque de atributos que integra a paternidade cresceu, em especial no que diz respeito ao tema do cuidado (Arilha, 1999;Fonseca, 2004;Fuller, 2000;Olavarria, 2000;Perucchi & Beirão, 2007;Souza & Benetti, 2009). Entretanto, pensar em paternidade(s) hoje, para além de simplesmente descrever uma realidade como se ela estivesse dada como um progresso, demanda problematizar as marcas que as paternidades carregam e os caminhos que tornaram possível uma maior atenção a essa prática.…”
Section: Paternidadesunclassified
“…A paternidade tem recebido destaque na literatura nas últimas décadas, especialmente no que tange às mudanças na família contemporânea, nas funções e nos papéis de homens e mulheres na sociedade (Souza & Benetti, 2009). À medida que as mulheres começaram a trabalhar fora de casa também se reconheceu a importância do pai para o desenvolvimento socioemocional e cognitivo da criança.…”
Section: Palabras-claveunclassified
“…À medida que as mulheres começaram a trabalhar fora de casa também se reconheceu a importância do pai para o desenvolvimento socioemocional e cognitivo da criança. Cada vez mais, o homem tem sido chamado ao âmbito privado/doméstico, destacando-se o discurso atual sobre os "novos" pais, que são mais afetuosos e participam diretamente da criação dos filhos, não apenas como provedores financeiros (Hennigen, & Guareschi, 2002;Souza & Benetti, 2009).…”
Section: Palabras-claveunclassified